Experimental applications of predictive modeling in archeology - Fejes Csaba (2005)
As Boast put it righteously "there is no basic difference in the way of human thinking between primitive and civilized cultures" starting off from the first intentional deeds, through the man of the medieval times up to the modern man of today. Settlements are generally established in areas where the environment is capable to support human needs. Thus the environment is an important influencing factor on the presence and distribution of humans, and this special relationship must be also quantifiable, analyzable in a given way. The major aim of the present study was to shed light onto various phenomena and their interrelations, the collective appearance or presence of which may refer to the existence of a prehistoric, mainly archean archeological site nearby with great certainty in an area with measurable physical properties or parameters. With the help of the exposed relationships a category map can be prepared for a less investigated area, which depicts the probability for the presence of a human settlement or archeological site. The gained results may be a good starting point for planning future excavations or any other kind of research. Thanks to the large-scale variety of data and procedures applied in the model, the collective usage of different analytical and statistical methods and approaches had to be utilized in our work ranging from the fields of geostatistics (logarithmic regression analysis) through geoinformatics (digital elevation model) to remote sensing (Landsat TM indexes).
Keywords: Természettudományok; Föld- és kapcsolódó környezettudományok